Boys and schooling : beyond structural reform - Lingard, Bob (Palgrave Macmillan, 2009)
Exploring the limitations of current approaches to addressing boys' education, this study illustrates how initiatives such as single-sex classes and schools for boys, the boy friendly curriculum and the call for more male teachers as role models have the potential to exacerbate rather than ameliorate the problems that boys are supposedly experiencing in schools. The book demonstrates that such approaches to boys' education have failed to acknowledge the significant impact of masculinity on both boys' and girls' lives and in turn have failed to address equity issues experienced by both minority boys and girls in schools. This study argues for new policies and a pedagogical reform agenda that engages with a more nuanced understanding of what constitutes good teaching and effective learning in schools for all students, while simultaneously interrogating the constrains imposed by dominant or stereotypical constructions of masculinity